Petits riens sophocléens : Antigone I: (v. 1–6, 7–8, 26–30, 71–74, 124–125, 148–153) - Liberman, Gauthier (Hyperboreus, 2022)
This is the first of five sets of text-critical, exegetical and sometimes metrical remarks on Antigone. These *Sophocleuncula are not only minute philological notes but they involve broader issues having a bearing on the interpretation and meaning of the drama as a whole (in this set we discuss the date of the composition and of the first performance of the tragedy, its place within the relevant trilogy and the idea that the relevant tetralogy came out second and not first in the dramatic contest). These remarks were composed with a view to drawing attention to a number of forgotten or unseen difficulties and to trying to address a number of seen but unsolved problems more efficaciously. The text and meaning of not a few other passages from other works of Sophocles or of other writers (e. g. Aeschylus’ Agamemnon) are also dealt with.